Novel modified carbon nanotubes as a selective sorbent for preconcentration and determination of trace copper ions in fruit samples. Issue 18 (4th August 2014) - Rezvani, Mehdi; Ebrahimzadeh, Homeira; Aliakbari, Azam; Khalilzadeh, Azita; Kasaeian, Mansoure; Amini, Mostafa M.
<x xml:space="preserve">Abstract</x> In this work, multiwalled carbon nanotubes were reacted with N‐[3‐(triet‐hoxysilyl)propyl]isonicotinamide to prepare pyridine‐functionalized carbon nanotubes. This novel sorbent was characterized by infrared spectroscopy, thermal and elemental analysis, and scanning electron microscopy. Functionalized carbon nanotubes were applied for the preconcentration and determination of copper ions using flame atomic absorption spectrometry. Various parameters such as sample pH, flow rate, eluent type and concentration, and its volume were optimized. Under optimal experimental conditions, the limit of detection, the relative standard deviation, and the recovery of the method were 0.65 ng/mL, 3.2% and 99.4%, respectively. After validating the method using standard reference materials, the new sorbent was applied for the extraction and determination of trace copper(II) ions in fruit samples.